Emotional Responses to Seductive Scientific Texts During Online and Offline Reading Tasks. Issue 1 (7th February 2022) - Mensink, Michael C.
ABSTRACT: Highly interesting but unimportant seductive details are commonly added to scientific texts, harming reader comprehension and memory for important content while also potentially evoking a strong emotional response. In two experiments, the effects of seductive details on participants' memory and emotional responses to seductive and nonseductive scientific texts were explored. In Experiment 1, participants read two scientific texts on related scientific topics with embedded seductive details and rated the sentences for importance and interest. In Experiment 2, participants read and then recalled one seductive and one nonseductive scientific text and rated the emotional responses they experienced during one reading task and one recall task. Participants rated seductive details as more interesting than important and recalled fewer scientific concepts from seductive texts compared to nonseductive texts. Although negative emotions were predictive of better recall of scientific concepts, the presence of seductive details and positive emotions were predictive of a reduced recall performance.